Isolation, screening and application of sauce-flavor bacteria from sauce-flavor Daqu - YU Mengting, SHI Hongli, LI Chunmao, WANG Shixin, LIU Huimin, SHU Nanxin, LIU Lin, ZHANG Peng, SUN Pengpeng, LONG Daizhou, GUO Songbo (Zhongguo niangzao)
The sauce-flavor bacteria were isolated and screened from the sauce-flavor Daqu through the dilution and coating plate method, protease production and high-temperature resistance test, as well as simulated solid-state fermentation. The strains were identified through morphological observation, physiological and biochemical tests, and molecular biology techniques. The volatile flavor components in the simulated solid-state fermentation products were analyzed using headspace solid-phase microextraction (HS-SPME) and GC-MS, and superior strains were screened to prepare a composite solid microbial agent for application in the production of cellar surface liquor. The results indicated that a total of 7 strains producing sauce-flavor were successfully isolated. After identification, strains XJ-26 and XJ-47 were Bacillus amyloliquefaciens, strains XJ-98, XJ-129, and XJ-169 were all Bacillus licheniformis, and strains XJ-8 and XJ-193 were Bacillus velezensis and Bacillus subtilis, respectively. The prevalent dominant volatile flavor compounds produced by these strains included 2,3,5,6-tetramethylpyrazine, 2,3,5-trimethylpyrazine, and 2,3-butanediol. Strains XJ-8, XJ-47, XJ-98, and XJ-193 were selected to make composite solid bacterial agents for fermentation to produce pit surface liquor. Compared with the control group, the reducing sugar and moisture content of the fermented grains unloading pit in the experimental group decreased significantly (P<0.05), and the contents of esters, aldehydes, pyrazines, and acids in the liquor samples all increased significantly (P<0.05). Among them, the contents of ethyl lactate, furfural, tetramethylpyrazine and acetic acid increased by 82.60%, 54.46%, 96.28% and 98.71%, respectively.